TRANSPARANSI DAN AKUNTABILITAS DALAM PENGELOLAAN DANA BOS (Studi Kasus pada MI Al-Islamiyah Atambua) - Fransiskus N. Naiola; Wilsna Rupilu; Agusta Amanda Wulandari; Tiffany N. P. Gah (P3M- Politeknik Negeri Kupang, 2021)
This research on the implementation of transparency and accountability in the management of BOS fund. Purpose of this study is to determine how the application of transparency and accountability in the management of BOS gunds. The benefit of this research is to wheter the MI Al-Islamiyah of Atambua has implemented the principles of transparency and accountability in the management of BOS funds. This research was conducted in MI Al-Islamiyah Atambua. The method used in this research in descriptive qualitative method where data collection using interview techniques, and document study, the interviewed several speakers including: Head of Schools, Treasurer and principal BOS fund, teacher and Student at MI Al-Islamiyah of Atambua. Research results show the application of transparency and accountability in the management of BOS is good enough, namely the existence of BOS funds RKAM in the planning. Compliance rule and technical instructions of use and implementation of BOS funds and the realization and successs, as well as the reporting and accountability of BOS funds to school, city/county, and government. The disbursement process in accordance with government regulations or technical guidelines in this management.